VALUATION METHODS OF BUSINESS REPUTATION (GOODWILL) UNDER ASSESSMENT OF INVESTMENT ATTRACTIVENESS OF THE BUSINESS ENTITY - Anikina Natali Anatolyevna (Advanced Engineering Research)
The paper covers the description of role of business reputation (goodwill) in the assessment of the investment attractiveness of a business entity. The methodology of the goodwill valuation which allows making investment decisions is taken into account. Advantages and disadvantages of the methods are stated. The fact that the discounted cash flows method is the most reliable method of the goodwill valuation is concluded.